واقع شبكة الحماية الاجتماعية في العراق و امكانيات تطويرها : محافظة نينوى أنموذجا - عدي سالم علي الطائي (PROSPECTIVE RESEARCHES, 2023)
The social safety net is considered one of the government tools, which can be used to reduce the poverty among the families. This role is not anew one because most of the government have done this many years ago, and we can find in all religions. The hard circumstances in Iraq influenced mechanisms of social safety. These hard circumstances left negative consequences on the effectiveness of social safety nets. Moreover, the new established social safety nets in Iraq lack enough money and it helpes but few of the relevant categories. As for Ninevah governorate level we have compared the elements of social safety net with its real outcomes. We have found a favorable distribution for urban families at the expense of the rurals, inspite of the high poverty rate in rural areas. Moreover, the poor coordination between the social caring agency in the governorate and the governmental relevant agencies, and decreasing awareness led to the increase of corruption and frand practices, a decreasing number of targeted families, and not to include the minimum number of the deserved families.